Rheological and thermal behaviors of commercial poly(aryletherketone)s. Issue 3 (18th September 2012) - White, Kevin L.; Jin, Lin; Ferrer, Nangelie; Wong, Minhao; Bremner, Tim; Sue, Hung‐Jue
Abstract The mechanical properties and thermal stability of several grades of poly(aryletherketone)s (PAEKs) were investigated using thermal, rheological, and dynamic mechanical characterization. Detailed rheological characterization revealed that several grades of poly(etheretherketone) (PEEK) exhibit relaxation behavior characteristic of a long‐chain branched structure. The potentially branched PEEKs showed greater mechanical damping behavior than the linear‐chain PEEKs. The molecular weight dependence on zero‐shear viscosity for several linear‐chain polymers indicates that the PEEKs behave as rigid chains in the melt. Differences in chain structure do not significantly influence dynamic mechanical behavior in the solid state but affect stability at elevated temperatures. The potentially branched PEEKs are most susceptible to oxidation in air, but exhibit much greater stability in nitrogen. Poly(etherketone) is highly susceptible to degradation in both air and nitrogen environments. Implications of this study for development of high‐performance PAEKs are discussed. POLYM. ENG. SCI. 2013. © 2012 Society of Plastics Engineers